Intellectual, neuropsychological, and behavioral functioning in children with tetralogy of Fallot - Miatton, Marijke; De Wolf, Daniël; François, Katrien; Thiery, Evert; Vingerhoets, Guy (The Journal of thoracic and cardiovascular surgery, 2007)
Although it is known that pediatric cardiac surgery holds risks for later development, few studies investigated the long-term development in children with tetralogy of Fallot. The purpose of this study was to define their intellectual capacities, neuropsychological profile, and behavioral functioning 6 to 12 years postoperatively. Patients (n = 18; age, 8 years, 3 months ± 1 year, 6 months) were examined with a short-form intelligence scale (Wechsler Intelligence Scale for Children, 3rd edition, Dutch version) and a neuropsychological assessment battery (NEPSY). Their parents completed a behavioral questionnaire. The patient group was compared with an acyanotic congenital heart disease group and a healthy control group. No significant differences between the patient group and the acyanotic group emerged. Compared with the healthy control group, children with tetralogy of Fallot showed significantly lower scores on the estimated Full Scale IQ ( P < .05) and on the NEPSY domains Language ( P < .01) and Sensorimotor Functioning ( P < .01). Also, the subtests Tower ( P < .05), Memory for Names ( P < .05), Narrative Memory ( P < .05), and Design Copy ( P < .05) elicited group differences. Parental reports revealed significantly higher scores on attention problems ( P < .05) and the total problem scale ( P < .05), as well as significantly lower school performances than those of healthy peers ( P < .01). In children with tetralogy of Fallot, we identified a lower estimated full-scale intelligence than in healthy peers and a neuropsychological profile characterized by primarily mild motor deficits and difficulties with language tasks. Parents of the children with tetralogy of Fallot indicated attention problems and rated the child’s school competencies to be lower than in healthy control subjects.